Knowledge Attitude and Willingness of Nursing Students Regarding HIV/AIDS Patient Care of Selected Nursing College of Banke District - Tulsa Sunar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
AIDS began with exposure to the HIV virus. A person infected with HIV causes progressive detoriation and dysfunction in cell mediated immunity and its most severe stage in the disease called AIDS. HIV related stigma and discrimination may prevent their access to treatment and other rights. This stigmatization and discrimination discourage individuals infected with HIV from contacting health and social services. This descriptive study entitled “Knowledge, Attitude and willingness of nursing students regarding HIV/AIDS patient care” was carried out on PCL nursing student at Nepalgunj Nursing Campus TU IOM, Banke. The main objective of this study was to find the level of knowledge, attitude and willingness regarding HIV/AIDS patient care among PCL nursing Students. Although research setting was selected conveniently, sample selection was done by using simple random sample technique through lottery method and 54 respondents were selected out of 136 students where all respondents were female. Self-administered semi- structured questionnaire technique was used as instrument for data collection. Collected data was analyzed and interpreted by using descriptive statistics like frequency, percentage, mean and standard deviation. This study shows, majority (63%) of the respondents had good knowledge and only few (18.5%) of the respondents had poor knowledge. majority (85.2%) of the respondents had positive attitude towards caring of HIV/AIDS patient likewise only (14.8%) had negative attitude. This study reveals mostly (88.9%) of the respondents were willing to take care of patient with HIV/AIDS. Similarly, majority (96.3%) of the participants were willing to accept the responsibility of HIV/AIDS patient care whereas 63% of the respondents were still willing to provide care even after exposure to HIV infected body fluids.